Differentiations in Gene Content and Expression Response to Virulence Induction Between Two Agrobacterium Strains - Haryono, Mindia; Cho, Shu-Ting; Fang, Mei-Jane; Chen, Ai-Ping; Chou, Shu-Jen; Lai, Erh-Min; Kuo, Chih-Horng (Frontiers in Microbiology, 2019)
Agrobacterium tumefaciens is important in biotechnology due to its ability to transform eukaryotic cells. Although the molecular mechanisms have been studied extensively, previous studies were focused on the model strain C58. Consequently, nearly all of the commonly used strains for biotechnology application were derived from C58 and share similar host ranges. To overcome this limitation, better understanding of the natural genetic variation could provide valuable insights. In this study, we conducted comparative analysis between C58 and 1D1609. These two strains belong to different genomospecies within the species complex and have distinct infectivity profiles. Genome comparisons revealed that each strain has >1,000 unique genes in addition to the 4,115 shared genes. Furthermore, the divergence in gene content and sequences vary among replicons. The circular chromosome is much more conserved compared to the linear chromosome. To identify the genes that may contribute to their differentiation in virulence, we compared the transcriptomes to screen for genes differentially expressed in response to the inducer acetosyringone. Based on the RNA-Seq results with three biological replicates, ~100 differentially expressed genes were identified in each strain. Intriguingly, homologous genes with the same expression pattern account for <50% of these differentially expressed genes. This finding indicated that phenotypic variation may be partially explained by divergence in expression regulation. In summary, this study characterized the genomic and transcriptomic differences between two representative Agrobacterium strains. Moreover, the short list of differentially expressed genes are promising candidates for future characterization, which could improve our understanding of the genetic mechanisms for phenotypic divergence.